2021
DOI: 10.3390/f12060722
|View full text |Cite
|
Sign up to set email alerts
|

New Representation of Plant Hydraulics Improves the Estimates of Transpiration in Land Surface Model

Abstract: Transpiration represents more than 30% of the global land–atmosphere water exchange but is highly uncertain. Plant hydraulics was ignored in traditional land surface modeling, but recently plant hydraulics has been found to play an essential role in transpiration simulation. A new physical-based representation of plant hydraulic schemes (PHS) was recently developed and implemented in the Common Land Model (CoLM). However, it is unclear to what extent PHS can reduce these uncertainties. Here, we evaluated the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…The present study further showed that the global fire count increment induced by PHS functions could be attributed to the elevated ecosystem water loss via plant transpiration and the resultant drier environment from the global perspective (Figure 8). Consistent with our results, the PHS configuration has been proven to increase plant transpiration at 81 FLUXNET sites across the globe [20] and over four different climatic subregions of China [21]. The PHS configuration uses water stress on leaf water potential to restrict transpiration; stress on transpiration can be induced by decreasing atmospheric moisture (e.g., increasing vapor pressure deficit) and soil water supply, and the latter was also regulated by root hydraulic redistribution (HR) processes [19].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The present study further showed that the global fire count increment induced by PHS functions could be attributed to the elevated ecosystem water loss via plant transpiration and the resultant drier environment from the global perspective (Figure 8). Consistent with our results, the PHS configuration has been proven to increase plant transpiration at 81 FLUXNET sites across the globe [20] and over four different climatic subregions of China [21]. The PHS configuration uses water stress on leaf water potential to restrict transpiration; stress on transpiration can be induced by decreasing atmospheric moisture (e.g., increasing vapor pressure deficit) and soil water supply, and the latter was also regulated by root hydraulic redistribution (HR) processes [19].…”
Section: Discussionsupporting
confidence: 83%
“…It is worth mentioning that the PHS configuration in CLM5 allows for hydraulic redistribution (HR) and compensatory root water uptake. Previous research has confirmed that the incorporation of PHS configuration into CLM5 improved the estimates of ecosystem water and carbon fluxes [19][20][21]. Moreover, the PHS-incorporated CLM5 model could well reproduce the global wildfire carbon emission derived from the satellite products [22], and it has advantages against other LSMs, because the CLM5 uniquely considered the seasonality of crop fires and simulated the burning of plant tissue and litter from peat fires and the drought-linked tropical deforestation and degradation fire [23].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…A natural application for our model framework is its incorporation into land‐surface models. So far, the incorporation of plant hydraulics into land‐surface models has been used to investigate the feedback between climate and vegetation in terms of water cycle during non‐stressed conditions and drought, yet mechanistic plant responses to excessive soil water content are still lacking in these models (Li et al, 2021 ; Nguyen et al, 2020 ). With climate change expected to enhance surface evaporation and atmospheric vapor accumulation, the intensity and duration of droughts as well as the chances of flooding are both increased, underlining the demand for a framework capable of integrating both drought and flooding responses of plants (Trenberth, 2011 ).…”
Section: Discussion Concluding Remarks and Outlookmentioning
confidence: 99%
“…A natural application for our model framework is its incorporation into land-surface models. So far, the incorporation of plant hydraulics into land-surface models has been used to investigate the feedback between climate and vegetation in terms of water cycle during non-stressed conditions and drought, yet mechanistic plant responses to excessive soil water content are still lacking in these models (Li et al, 2021;Nguyen et al, 2020). With climate change expected to enhance surface evaporation and atmospheric vapor accumulation, the intensity and duration of droughts as well as the chances of flooding are both increased, underlining the demand for a framework capable of integrating both drought and flooding responses of plants (Trenberth, 2011).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%